Pemenuhan Hak Upah Tenagakerja Dalam Rangka Mendukung Investasi di Kota Batam - Elza Syarief; Ampuan Situmeang; Sugiyarto Sugiyarto (Fakultas Hukum, Universitas Internasional Batam, 2015)
This study to analyze Undang-Undang No. 13 Year 2003 about Employment to organize the labors in order to support the investment at Batam City. This research used juridical sociological law framework. The research showed that the labors wage system at Batam City was adapted to the appropriate living standard at Batam City. The minimum wages at Batam City increased regularly and gave a negative impact in investment climate at Batam City because foreign companies had to pay a high value of wages. Because of that, the solution offered to Batam City government was to create a safe environment and stable labors wage.